Multitasking: Executive Functioning in Dual-Task and Task Switching Situations - Mike Wendt (Frontiers Research Topics, 2018)
Multitasking refers to performance of multiple tasks. The most prominent types of multitasking are situations including either temporal overlap of the execution of multiple tasks (i.e., dual tasking) or executing multiple tasks in varying sequences (i.e., task switching). In the literature, numerous attempts have aimed at theorizing about the specific characteristics of executive functions that control interference between simultaneously and/or sequentially active component of task-sets in these situations. However, these approaches have been rather vague regarding explanatory concepts (e.g., task-set inhibition, preparation, shielding, capacity limitation), widely lacking theories on detailed mechanisms and/ or empirical evidence for specific subcomponents. The present research topic aims at providing a selection of contributions on the details of executive functioning in dual-task and task switching situations. The contributions specify these executive functions by focusing on (1) fractionating assumed mechanisms into constituent subcomponents, (2) their variations by age or in clinical subpopulations, and/ or (3) their plasticity as a response to practice and training.